Proud to Not Own Stocks: How Identity Shapes Financial Decisions - Luca Henkel; Christian Zimpelmann (Institute of Labor Economics (IZA), 2023)
This paper introduces a key factor influencing households' decision to invest in the stock market: how people view stockholders. Using surveys we conducted with nearly 8,500 individuals from eleven countries, we document that a large majority of respondents view stockholders negatively – they are perceived as greedy, gambler-like, and selfish individuals. We then provide experimental evidence that such perceptions of identity-relevant characteristics causally influence decision- making: if people view stockholders more negatively, they are less likely to choose stock-related investments. Furthermore, by linking survey and administrative data, we show that negative perceptions strongly predict households' stock market participation, more so than leading alternative determinants. Our findings provide a novel explanation for the puzzlingly low stock market participation rates around the world, new perspectives on the malleability of financial decision-making, and evidence for the importance of identity in economic decision-making.
Keywords: G41; G51; D14; D83; 330; identity; perceptions; stock market participation; financial decision-making